(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2024)
Background: The Effectiveness of CO2 laser tonsillectomy is not conclusively known. The current study aimed to determine its effectiveness compared to the cold steel dissection for tonsillectomy in children. Methods: This interventional study was done in the Department of Otolaryngology of AL-Yarmouk Teaching Hospital, Baghdad, Iraq. It was done in 80 children eligible for tonsillectomy, evenly divided into cold steel dissection tonsillectomy (group A) and CO2 laser tonsillectomy (group B). The surgical outcomes of the two groups were analysed for operative time, intra-operative blood loss, post-operative pain, bleeding, tonsillar fossae sloughing, and the time taken to return to daily activity. Results: The CO2 tonsillectomy group showed better effectiveness in terms of operative time (37.6 versus 19.5 min), intra-operative blood loss (42.7 versus 15.8 mL), postoperative pain at days 1, 7 and 14), and tonsillar bed sloughing (25.0% versus 32.5%). However, primary and secondary postoperative haemorrhages were similar between the groups. Conclusions: Although the results are not generalisable, the CO2 laser tonsillectomy was more effective than the cold steel dissection tonsillectomy.